2022
DOI: 10.1038/s41598-022-08706-y
|View full text |Cite
|
Sign up to set email alerts
|

Genome wide association study of frost tolerance in wheat

Abstract: Winter wheat growing areas in the Northern hemisphere are regularly exposed to heavy frost. Due to the negative impact on yield, the identification of genetic factors controlling frost tolerance (FroT) and development of tools for breeding is of prime importance. Here, we detected QTL associated with FroT by genome wide association studies (GWAS) using a diverse panel of 276 winter wheat genotypes that was phenotyped at five locations in Germany and Russia in three years. The panel was genotyped using the 90 K… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 88 publications
1
9
0
1
Order By: Relevance
“…Moreover, eight candidate genes associated with abiotic stresses were reported, with three significantly linked to LTG: CsaV3_1G044080 (pentatricopeptide repeat‐containing protein) for gLTG1.2 , CsaV3_4G013480 (RING‐type E3 ubiquitin transferase) for gLTG4.1 , and CsaV3_5G029350 (serine/threonine‐protein kinase) for gLTG5.2 (Li et al, 2023a). Frost tolerance (FroT) QTL were identified in 276 winter wheat genotypes previously phenotyped at field locations in Germany and Russia (Soleimani et al, 2022). From a pool of 17,566 SNPs, 53 were significantly associated with FroT, corresponding to 23 QTL regions on 11 chromosomes (1A, 1B, 2A, 2B, 2D, 3A, 3D, 4A, 5A, 5B, and 7D).…”
Section: Omics‐driven Breeding For Temperature‐smart Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, eight candidate genes associated with abiotic stresses were reported, with three significantly linked to LTG: CsaV3_1G044080 (pentatricopeptide repeat‐containing protein) for gLTG1.2 , CsaV3_4G013480 (RING‐type E3 ubiquitin transferase) for gLTG4.1 , and CsaV3_5G029350 (serine/threonine‐protein kinase) for gLTG5.2 (Li et al, 2023a). Frost tolerance (FroT) QTL were identified in 276 winter wheat genotypes previously phenotyped at field locations in Germany and Russia (Soleimani et al, 2022). From a pool of 17,566 SNPs, 53 were significantly associated with FroT, corresponding to 23 QTL regions on 11 chromosomes (1A, 1B, 2A, 2B, 2D, 3A, 3D, 4A, 5A, 5B, and 7D).…”
Section: Omics‐driven Breeding For Temperature‐smart Plantsmentioning
confidence: 99%
“…From a pool of 17,566 SNPs, 53 were significantly associated with FroT, corresponding to 23 QTL regions on 11 chromosomes (1A, 1B, 2A, 2B, 2D, 3A, 3D, 4A, 5A, 5B, and 7D). The QTL regions on chromosome 5A were strongly responsible for FroT (Soleimani et al, 2022).…”
Section: Omics‐driven Breeding For Temperature‐smart Plantsmentioning
confidence: 99%
“…In wheat, GWAS analyses led to the identification of seven QTLs associated with cold tolerance using a diversity panel of 450 Canadian wheat varieties (Chen et al., 2019). Also, 23 QTLs localized on 11 chromosomes (1A, 1B, 2A, 2B, 2D, 3A, 3D, 4A, 5A, 5B, and 7D) were identified by GWAS using a diverse panel of 276 winter wheat accessions (Soleimani et al., 2022). Using GWAS, one major additive effect QTL was identified on wheat chromosome 5B (Zhao et al., 2013).…”
Section: Advances In Omics Approaches For Uncovering Cold Tolerance I...mentioning
confidence: 99%
“…Although Fr-1 and Fr-2 jointly regulate frost resistance in wheat, speci c biological mechanisms remain unclear (Zhu et al, 2014, Galiba et al, 2009. Recently, QTL mapping and genome-wide association studies (GWAS) have revealed new frost resistance hotspots in wheat's homologous groups 4 and 7, but these loci are not su cient to meet improvement needs (Zhang et al, 2022b, Zhao et al, 2020, Soleimani et al, 2022. Additionally, there is only one well-de ned cold signaling pathway, the inducer of CBF expression (ICE)-CBF cold response (COR) pathway (Shi et al, 2018, Liu et al, 2019, emphasizing the urgent need for further research on the genetics and molecular biology of wheat frost resistance.…”
Section: Introductionmentioning
confidence: 99%